PERANCANGAN SISTEM PENENTUAN SIMILARITY KODE PROGRAM PADA BAHASA C DAN PASCAL DENGAN MENGGUNAKAN ALGORITMA RABIN-KARP - Surahman, Ade Mirza (Jurusan Informatika Universitas Tanjungpura, 2013)
This research aims to design and implement an application that can determine the percentage of similarity to the C code and post using Rabin-Karp algorithm. In this application the input use is a code C and Pascal who type *. C and *. Pas, while the output of the application is in the form of percentage similarity of both the tested code and the processing time required in each process. The results of this study are called